Copper-indium-gallium-selenium power generation glass and preparation method thereof

The vulcanization treatment on the surface of the CIGS absorbing layer by laser heating method solved the problem of difficulty in controlling the position of sulfur elements in CIGS power generation glass, forming a "V"-shaped gradient band gap, which improved the photoelectric conversion efficiency and battery performance.

CN119133318AActive Publication Date: 2024-12-13CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD +3
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411265493.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

During the rapid heat treatment process of existing copper indium gallium selenide (CIGS) power generation glass, the competitive reaction between sulfur and selenium is difficult to accurately control the vulcanization position, affecting battery efficiency, and IR infrared heating causes selenium to be inside and at the bottom of the absorbing layer. Instead, increase the minimum energy gap, reduce short circuit current and conversion efficiency.

Method used

The surface of the CIGS absorbing layer is vulcanized under the atmosphere of sulfur-containing gas and inert gas by laser heating. The formation of the vulcanized layer is controlled through lattice laser heating and Daman grating technology, so as to limit the reaction depth of S element and avoid the MoS2 Generate, form a "V"-shaped gradient band gap to improve electron transmission.

Benefits of technology

It improves the photoelectric conversion efficiency of CIGS power generation glass, enhances the open circuit voltage and filling factor, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133318A_ABST
    Figure CN119133318A_ABST
Patent Text Reader

Abstract

The invention provides copper-indium-gallium-selenium power generation glass and a preparation method thereof.The preparation method comprises a vulcanization method for the surface of a copper-indium-gallium-selenium absorption layer, and the vulcanization method comprises the steps that a substrate comprising the CIGS absorption layer is cooled to 20-100 DEG C; and in the atmosphere of sulfur-containing gas and inert gas, raising the temperature of the surface of the CIGS absorption layer to 550-600 DEG C by adopting a laser heating method, and then reducing the temperature to 20-100 DEG C to obtain the vulcanization layer. The invention also provides a vulcanization method and a vulcanization device for the surface of the CIGS absorption layer, and a preparation device for the CIGS power generation glass. By adopting the preparation method of the copper-indium-gallium-selenium power generation glass, the photoelectric conversion efficiency of the copper-indium-gallium-selenium power generation glass can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular to a copper indium gallium selenide power generation glass and a preparation method thereof. Background Art

[0002] Copper indium gallium selenide (CIGS) power generation glass is a compound semiconductor solar cell and one of the thin-film solar cells with the highest photoelectric conversion efficiency. It has the advantages of high light absorption coefficient, high conversion efficiency, good stability, strong radiation resistance, good weak light performance and adjustable optical band gap. It is considered to be the most promising thin-film solar cell for large-scale application.

[0003] The CIGS cell structure is mainly composed of glass / back electrode layer / absorption layer / buffer layer / window layer / transparent conductive layer. The absorption layer is the most important component of the CIGS cell. Common absorption layer preparation methods include co-evaporation, sputtering prefabricated layer and then selenization, electroplating prefabricated layer and then selenization, and printing. At present, the market mostly uses the sputtering prefabricated layer and then selenization method to mass produce CIGS power generation glass. The process includes: prefabricated layer preparation / Se evaporation / rapid thermal treatment. Among them, rapid thermal treatment is the most critical link in the preparation of the absorption layer. The quality of rapid thermal treatment directly determines the quality of the absorption layer.

[0004] The large-scale mass production rapid thermal processing equipment of the sputtering-first-selenization method basically adopts IR infrared heating to selenize and sulfurize the prefabricated layer. In the N2 environment, H2S gas is introduced to achieve rapid annealing process in a short time to prepare high-quality CIGS absorption layer film. In the process of rapid thermal treatment, sulfur and selenium are in a competitive relationship and replace each other. Although this technology can increase the band gap of the film surface by obtaining a layer of CIGS film with a high band gap width on the surface of the CIGS film, because IR infrared heating is to radiate and heat the soda-lime glass at the same time, the temperature of the whole glass is evenly heated, so that sulfur will not only replace the selenium in CIGS on the surface of the absorption layer, but also the selenium inside and at the bottom of CIGS, resulting in an increase in the minimum energy gap in CIGS, thereby reducing the short-circuit current. In addition, it will replace the selenium in the bottom MoSe2 to generate a part of high-resistance MoS2, resulting in higher resistance and reduced component conversion efficiency. How to accurately control the sulfurization position of the copper indium gallium selenide absorption layer, as well as the degree of sulfurization, to achieve controllability and targeting of the sulfurization operation is a major technical difficulty currently faced. Summary of the invention

[0005] The purpose of this application is to provide a copper indium gallium selenide power generation glass and a preparation method thereof, which can accurately control the sulfurization position of the copper indium gallium selenide absorption layer and the degree of sulfurization to improve the photoelectric conversion efficiency of CIGS power generation glass. In order to prepare products with high conversion efficiency and excellent input-output ratio, and provide technical support for the society to achieve green and low-carbon transformation. The specific technical solution is as follows:

[0006] The first aspect of the present application provides a method for sulfurizing the surface of a CIGS absorption layer, which comprises: cooling a substrate including a CIGS absorption layer to 20 to 100° C.; in an atmosphere of sulfur-containing gas and inert gas, using a laser heating method to raise the temperature of the surface of the CIGS absorption layer to 550 to 600° C., and then cooling it to 20 to 100° C. to obtain a sulfurized layer.

[0007] Preferably, the laser heating method adopts dot-matrix laser heating.

[0008] Preferably, the volume ratio of the sulfur-containing gas to the inert gas is 1:2 to 1:3.

[0009] Preferably, the laser wavelength of the laser heating method is 8-12 μm, the scanning speed is 20-30 mm / s, and the output power is 60-100 W.

[0010] Preferably, the laser irradiation depth of the laser heating method is 1.0-2.0 μm.

[0011] Preferably, the sulfur-containing gas is selected from at least one of H2S and sulfur vapor; and the inert gas is selected from at least one of nitrogen, argon and helium.

[0012] Preferably, the heating rate of the laser heating method is 40-50° C. / s.

[0013] Preferably, the percentage of the number of S element atoms on the surface of the absorbing layer after vulcanization to the total number of atoms of the absorbing layer surface after vulcanization is 6-10%, preferably 6-8%, and more preferably 6-7%; the percentage of the mass of S element at the bottom of the absorbing layer after vulcanization to the total mass of the elements at the bottom of the absorbing layer after vulcanization is ≤0.03%.

[0014] The second aspect of the present application provides a vulcanization device for the surface of a CIGS absorption layer, comprising: a transmission cavity, wherein an exhaust system, an inert gas intake system and a sulfur-containing gas intake system are connected to the outside of the transmission cavity, a laser emitter, a Dammann grating and a transmission device are arranged in the transmission cavity, the transmission device transmits a substrate including a CIGS absorption layer to the transmission cavity, and the target laser emitted by the laser emitter is irradiated to the surface of the CIGS absorption layer through the Dammann grating.

[0015] Preferably, a first cavity flap valve and a second cavity flap valve are respectively provided on both sides of the transfer cavity.

[0016] Preferably, the sulfur-containing gas intake system is selected from at least one of an H2S intake system and a sulfur vapor intake system; and the inert gas intake system is selected from at least one of a nitrogen intake system, an argon intake system and a helium intake system.

[0017] Preferably, the Dammann grating is rotatable so that an angle α between the target laser and the Dammann grating satisfies 0°<α≤90°.

[0018] The third aspect of the present application provides a method for preparing CIGS power generation glass, which comprises:

[0019] preparing a substrate, and preparing a back electrode layer on the upper surface of the substrate;

[0020] Preparing a CIGS absorption layer on the upper surface of the back electrode layer;

[0021] Sulfurizing the surface of the CIGS absorber layer, comprising: using the sulfurization method described in the first aspect of the present application or the sulfurization device described in the second aspect of the present application to sulfurize the surface of the CIGS absorber layer to obtain the sulfurized layer;

[0022] Preparing a buffer layer on the upper surface of the vulcanized layer;

[0023] Preparing a high resistance layer on the upper surface of the buffer layer;

[0024] Preparing a transparent conductive layer on the upper surface of the high resistance layer;

[0025] The CIGS power generation glass is obtained by installing bus bars on both sides of the substrate to draw out current.

[0026] Preferably, the material of the substrate is selected from soda-lime glass, flexible metal foil or polyimide; the material of the back electrode layer is selected from molybdenum (Mo), copper zinc (CZ++) or nickel (Ni); the material of the buffer layer is selected from indium sulfide or cadmium sulfide; the material of the high resistance layer is selected from intrinsic zinc oxide (i-ZO) or magnesium-doped zinc oxide (MZO); the material of the transparent conductive layer is selected from aluminum-doped zinc oxide, boron-doped zinc oxide or indium tin oxide (ITO).

[0027] Preferably, the thickness of the substrate is 2-4 mm; the thickness of the back electrode layer is 0.2-1 μm; the thickness of the absorption layer is 1.5-2.0 μm; the thickness of the buffer layer is 0.05-0.1 μm; the thickness of the high resistance layer is 0.05-0.1 μm; and the thickness of the transparent conductive layer is 0.5-1.5 μm.

[0028] Preferably, the substrate is prepared by a float process, a calendaring process or an overflow down-draw process;

[0029] The back electrode layer is prepared by magnetron sputtering, chemical vapor deposition (CVD) or electroplating;

[0030] The CIGS absorption layer is prepared by a sputtering and then selenization method or a co-evaporation method;

[0031] The buffer layer is prepared by evaporation or chemical water bath deposition;

[0032] The high resistance layer is prepared by radio frequency magnetron sputtering or pulsed DC sputtering;

[0033] The transparent conductive layer is prepared by a DC magnetron sputtering method, a pulsed DC sputtering method or a radio frequency magnetron sputtering method.

[0034] The fourth aspect of the present application provides a device for preparing CIGS power generation glass, which includes the sulfurization device described in the second aspect of the present application.

[0035] The fifth aspect of the present application provides CIGS power generation glass prepared by the preparation method described in the third aspect of the present application or the preparation device described in the fourth aspect of the present application.

[0036] Beneficial effects of this application:

[0037] The present application provides a method and device for sulfurizing the surface of a CIGS absorption layer. By using a laser heating method to perform sulfurization treatment on the surface of the CIGS absorption layer, the reaction depth of the S element replacing the Se element can be limited, and sulfurization can occur on the surface of the CIGS absorption layer, thereby avoiding excessive S content inside and at the bottom of the CIGS absorption layer, and avoiding excessive MoS2 with poorer conductivity at the bottom of the CIGS absorption layer, so that the Ga at the bottom of the CIGS absorption layer and the S at the top of the CIGS absorption layer form a "V"-shaped gradient band gap, which enhances electron transmission, increases the open circuit voltage and fill factor, and thus improves the photoelectric conversion efficiency of the CIGS power generation glass. The present application further provides a method and device for preparing CIGS power generation glass, and the CIGS power generation glass has a high conversion efficiency.

[0038] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0040] Figure 1 A device for surface sulfurization of a CIGS absorber layer according to an embodiment of the present application;

[0041] Figure 2 A schematic diagram of the unit structure of a CIGS power generation glass according to an embodiment of the present application;

[0042] Figure 3 This is a flow chart of the preparation process of CIGS power generation glass according to an embodiment of the present application.

[0043] In the figure, there are a transfer chamber 1, a first flap valve 2, an inert gas intake system 3, a sulfur-containing gas intake system 4, an exhaust system 5, a laser emitter 6, a Dammann grating 7, a second flap valve 8, a transfer device 9, a substrate 10 including a CIGS absorption layer, a substrate 121, a back electrode layer 122, an absorption layer 123, a CIGS absorption layer 1231, a sulfide layer 1232, a buffer layer 124, a high resistance layer 125, and a transparent conductive layer 126. DETAILED DESCRIPTION

[0044] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0045] In a first aspect, the present application provides a method for vulcanizing the surface of a CIGS absorption layer, which comprises: cooling a substrate including a CIGS absorption layer to 20 to 100° C.; in an atmosphere of sulfur-containing gas and inert gas, using a laser heating method to raise the temperature of the surface of the CIGS absorption layer to 550 to 600° C., and then cooling it to 20 to 100° C. to obtain a vulcanized layer.

[0046] The inventors discovered in their research that after the CIGS absorption layer is prepared, the substrate including the CIGS absorption layer is cooled to 20-100°C, and the CIGS absorption layer on the upper surface of the substrate is quickly heated by laser heating in an atmosphere of sulfur-containing gas and inert gas. Since the laser heating speed is fast, the heat-affected zone is small, and it is surface scanning heating quenching, the material can be heated and cooled at high speed, so sulfurization is only performed on the surface of the CIGS absorption layer. This not only does not cause S to replace Se inside the CIGS absorption layer, but also avoids the generation of MoS2 with poor conductivity at the bottom of the CIGS absorption layer, thereby improving the photoelectric conversion efficiency of the CIGS power generation glass.

[0047] Preferably, the laser heating method adopts dot-matrix laser heating.

[0048] The inventors found in their research that the selection of dot matrix laser heating can achieve adjustable heating rate, fast heating speed and cooling speed, more uniform heating, etc. In this application, the specific method of realizing dot matrix laser is not particularly limited, as long as the purpose of this application can be achieved. For example, the laser is dot matrix differentiated by Dammann grating.

[0049] Preferably, the volume ratio of the sulfur-containing gas to the inert gas is 1:2 to 1:3.

[0050] The inventors have found in their research that by limiting the volume ratio of the sulfur-containing gas to the inert gas within the scope of the present application, an excess of inert gas can serve as a protective gas and also allow the sulfur-containing gas to more fully contact and react with the CIGS absorption layer.

[0051] Preferably, the wavelength of the laser is 8-12 μm, the scanning speed is 20-30 mm / s, and the output power is 60-100 W.

[0052] The inventors found in their research that the wavelength, scanning speed and output power of the laser within the scope of this application can better achieve the sulfurization treatment of the surface of the CIGS absorption layer. Too high laser output power may cause the substrate temperature to be too high, resulting in burn damage, while too low laser output power may result in insufficient temperature; too fast or too slow scanning speed may result in uneven substrate temperature.

[0053] Preferably, the laser irradiation depth of the laser heating method is 1.0-2.0 μm.

[0054] Preferably, the sulfur-containing gas is selected from at least one of H2S and sulfur vapor; and the inert gas is selected from at least one of nitrogen, argon and helium.

[0055] Preferably, the heating rate of the laser heating method is 40-50° C. / s.

[0056] Preferably, the temperature of the surface of the CIGS absorption layer is raised to 550-600°C by laser heating, maintained for 80-120s, and then cooled to 20-100°C.

[0057] In the present application, there is no particular limitation on the cooling method, as long as the purpose of the present application can be achieved. For example, air cooling, water cooling, oil cooling, etc. are used for cooling.

[0058] Preferably, the percentage of the number of S element atoms on the surface of the absorbing layer after vulcanization to the total number of atoms of the absorbing layer surface after vulcanization is 6-10%, preferably 6-8%, and more preferably 6-7%; the percentage of the mass of S element at the bottom of the absorbing layer after vulcanization to the total mass of the elements at the bottom of the absorbing layer after vulcanization is ≤0.03%.

[0059] The inventors found in their research that when the degree of sulfurization of the present application is controlled within the above range, S can replace Se on the surface of the film layer, thereby increasing the surface band gap.

[0060] In the present application, the surface of the absorption layer is the upper surface of the absorption layer; the bottom of the absorption layer is the upper surface after the absorption layer is immersed in a 5-20wt% aminosulfonic acid aqueous solution for 2-3 minutes to corrode the metal layer on the surface of the absorption layer.

[0061] like Figure 1 As shown, the second aspect of the present application provides a vulcanization device for the surface of a CIGS absorption layer, which includes: a transmission cavity 1, the transmission cavity 1 is connected to an exhaust system 5, an inert gas intake system 3 and a sulfur-containing gas intake system 4, a laser emitter 6, a Dammann grating 7 and a transmission device 9 are arranged in the transmission cavity 1, and the transmission device 9 transmits a substrate 10 including a CIGS absorption layer to the transmission cavity 1, and the target laser emitted by the laser emitter 6 is irradiated to the surface of the CIGS absorption layer through the Dammann grating 7.

[0062] Preferably, a first cavity flap valve 2 and a second cavity flap valve 8 are respectively provided on both sides of the transfer cavity 1 .

[0063] Preferably, the sulfur-containing gas intake system 4 is selected from at least one of an H2S intake system and a sulfur vapor intake system; the inert gas intake system 3 is selected from at least one of a nitrogen intake system, an argon intake system and a helium intake system.

[0064] Preferably, the wavelength of the target laser emitted by the laser emitter 6 is 8-12 μm, the scanning speed is 20-30 mm / s, and the output power is 60-100 W.

[0065] In the present application, the Dammann grating 7 is used to process the target laser to form a uniform lattice laser; preferably, the irradiation depth of the lattice laser is 1.0-2.0 μm, and the heating rate is 40-50°C / s. The inventors found in their research that the Dammann grating 7 processes the target laser to form a uniform lattice laser, which can achieve adjustable heating rate, fast heating speed and cooling speed, and more uniform heating.

[0066] Preferably, the Dammann grating 7 is rotatable so that the angle α between the target laser and the Dammann grating 7 satisfies 0°<α≤90°.

[0067] It should be noted that the Dammann grating 7 is rotatable mainly to achieve targeted vulcanization.

[0068] Preferably, the structure of the grating in the Dammann grating is adjustable to achieve phase adjustment of the wavelength light beam.

[0069] The inventors found in their research that the Dammann grating can achieve phase adjustment of a wavelength light beam by adjusting the structure of the grating. In the present application, the specific method of adjusting the grating is not particularly limited, as long as the purpose of the present application can be achieved. For example, the phase adjustment of a specific wavelength light beam can be achieved by adjusting the spacing and thickness of the metal wire and the slit.

[0070] like Figure 2 As shown, the third aspect of the present application provides a method for preparing CIGS power generation glass, which comprises:

[0071] A substrate 121 is prepared, and a back electrode layer 122 is prepared on the upper surface of the substrate 121;

[0072] Prepare a CIGS absorption layer 1231 on the upper surface of the back electrode layer 122;

[0073] Sulfurizing the surface of the CIGS absorption layer 1231, comprising: using the sulfurization method described in the first aspect of the present application or the sulfurization device described in the second aspect of the present application to sulfurize the surface of the CIGS absorption layer to obtain the sulfurized layer 1232;

[0074] Prepare a buffer layer 124 on the upper surface of the sulfide layer 1232;

[0075] Prepare a high resistance layer 125 on the upper surface of the buffer layer 124;

[0076] Prepare a transparent conductive layer 126 on the upper surface of the high resistance layer 125;

[0077] The CIGS power generation glass is obtained by installing bus bars on both sides of the substrate to draw out current.

[0078] like Figure 1 As shown, in one embodiment of the present application, the sulfurization includes using a sulfurization device to perform a sulfurization treatment on the surface of the CIGS absorption layer, and the sulfurization device includes:

[0079] A transmission cavity 1, the transmission cavity 1 is connected to an exhaust system 5, an inert gas intake system 3 and a sulfur-containing gas intake system 4, a laser emitter 6, a Dammann grating 7 and a transmission device 9 are arranged in the transmission cavity 1, the transmission device 9 transmits a substrate 10 including a CIGS absorption layer into the transmission cavity 1, and the target laser emitted by the laser emitter 6 is irradiated to the surface of the CIGS absorption layer through the Dammann grating 7; a first cavity flap valve 2 and a second cavity flap valve 8 are respectively arranged on both sides of the transmission cavity 1.

[0080] In the present application, the substrate 10 including the CIGS absorption layer includes, from bottom to top, a substrate 121 , a back electrode layer 122 and an absorption layer 123 ; the surface of the absorption layer 123 is the upper surface of the absorption layer.

[0081] Preferably, the sulfur-containing gas intake system is selected from at least one of an H2S intake system and a sulfur vapor intake system; and the inert gas intake system is selected from at least one of a nitrogen intake system, an argon intake system and a helium intake system.

[0082] Preferably, the conveying device 9 is selected from a conveying roller or a conveying belt. The present application has no particular limitation on the number of the conveying rollers, as long as the substrate 10 including the CIGS absorption layer can be conveyed into the conveying cavity 1 and rotated at a predetermined speed to complete the vulcanization reaction; illustratively, the number of the conveying rollers is 5 to 20.

[0083] Preferably, the vulcanization treatment comprises:

[0084] The transfer chamber 1 is placed in a slightly negative pressure state through the exhaust system 5; the inert gas is introduced through the inert gas intake system 3 to adjust the pressure of the transfer chamber 1 to 400-600 mbar; the exhaust system 5 is then used to adjust the pressure of the transfer chamber 1 to 4-6 mbar, the above steps are repeated three times, and finally the exhaust system 5 is used to adjust the pressure of the transfer chamber 1 to 0.1-0.3 mbar;

[0085] The first flap valve 2 is opened, and the conveying device 9 conveys the substrate 10 including the CIGS absorption layer into the conveying chamber 1;

[0086] Inert gas and sulfur-containing gas are introduced into the transfer cavity 1 through the inert gas intake system 3 and the sulfur-containing gas intake system 4; in the atmosphere of the inert gas and sulfur-containing gas, the target laser emitted by the laser emitter 6 is irradiated to the surface of the CIGS absorption layer in a dot matrix through the Dammann grating 7, so that the temperature of the surface of the CIGS absorption layer rises to 550-600° C. for heating; inert gas is introduced through the inert gas intake system 3 to make the pressure of the transfer cavity 1 reach 400-600 mbar; the pressure of the transfer cavity 1 is adjusted to 4-6 mbar through the exhaust system 5, and the above steps are repeated three times, and finally the pressure of the transfer cavity 1 is adjusted to 0.1-0.3 mbar through the exhaust system 5;

[0087] The laser emitter 6 is turned off, and the air is circulated through the exhaust system 5 to evacuate and release air, and then the surface temperature is reduced to 20-100°C to obtain a vulcanized layer; the second flap valve 8 is opened, and the conveying device 9 conveys the substrate 10 including the CIGS absorption layer to the outside of the conveying chamber 1 to complete the vulcanization.

[0088] In the present application, the slightly negative pressure is 900-1000 mbar. The air extraction system 5 makes the transfer chamber 1 in a slightly negative pressure state in order to prevent harmful gases from overflowing.

[0089] Preferably, the volume ratio of the sulfur-containing gas to the inert gas is 1:2 to 1:3.

[0090] Preferably, the wavelength of the laser is 8-12 μm, the scanning speed is 20-30 mm / s, and the output power is 60-100 W.

[0091] Preferably, the laser irradiation depth of the laser heating method is 1.0-2.0 μm.

[0092] Preferably, the sulfur-containing gas intake system is selected from at least one of an H2S intake system and a sulfur vapor intake system; and the inert gas intake system is selected from at least one of a nitrogen intake system, an argon intake system and a helium intake system.

[0093] Preferably, the heating rate of the laser heating method is 40-50° C. / s.

[0094] It should be noted that the heating rate is controlled by laser power and scanning speed.

[0095] Preferably, the percentage of the number of S element atoms on the surface of the absorbing layer after vulcanization to the total number of atoms of the absorbing layer surface after vulcanization is 6-10%, preferably 6-8%, and more preferably 6-7%; the percentage of the mass of S element at the bottom of the absorbing layer after vulcanization to the total mass of the elements at the bottom of the absorbing layer after vulcanization is ≤0.03%.

[0096] Preferably, the Dammann grating is rotatable so that an angle α between the target laser and the Dammann grating satisfies 0°<α≤90°.

[0097] Preferably, the structure of the grating in the Dammann grating is adjustable to achieve phase adjustment of the wavelength light beam.

[0098] The inventors found in their research that the Dammann grating can achieve phase adjustment of a wavelength light beam by adjusting the structure of the grating. In the present application, the specific method of adjusting the grating is not particularly limited, as long as the purpose of the present application can be achieved. For example, the phase adjustment of a specific wavelength light beam can be achieved by adjusting the spacing and thickness of the metal wire and the slit.

[0099] In the present application, there is no particular limitation on the conveying speed of the conveying device 9 as long as the purpose of the present application can be achieved. For example, the conveying device 9 conveys the substrate 10 including the CIGS absorption layer to the conveying chamber 1 at a speed of 4-8 m / min.

[0100] Preferably, the material of the substrate 121 is selected from soda-lime glass, flexible metal foil or polyimide; the material of the back electrode layer 122 is selected from Mo, CZ++ or Ni; the material of the buffer layer 124 is selected from indium sulfide or cadmium sulfide; the material of the high resistance layer 125 is selected from intrinsic zinc oxide or magnesium-doped zinc oxide; the material of the transparent conductive layer 126 is selected from aluminum-doped zinc oxide, boron-doped zinc oxide or indium tin oxide.

[0101] In the present application, the flexible metal foil may be selected from at least one of silver foil, stainless steel foil or aluminum foil.

[0102] Preferably, the material of the substrate 121 is selected from soda-lime glass. The inventors found in their research that the substrate material selected in the present application contains trace elements Na, which plays an important role in grain orientation and film formation effect. During the growth of CIGS thin film, Na will diffuse from the substrate through the Mo electrode layer into the CIGS absorption layer. The CIGS thin film grown on the soda-lime glass substrate has a smoother surface, closely arranged grains, clear orientation, and good film adhesion.

[0103] Preferably, the material of the back electrode layer 122 is selected from Mo. In the present application, the material of the back electrode layer is preferably Mo, which has relatively stable chemical properties and very good adhesion to the substrate; Mo has good electrical conductivity and is not easy to penetrate and diffuse into the CIGS absorption layer at high temperatures; Mo has a high reflectivity, so it can absorb secondary light and reduce the interface state between the two; from the perspective of the energy band, an appropriate amount of MoSe2 is formed between Mo and the CIGS absorption layer, which can reduce the recombination of electrons at Mo and CIGS and reduce the contact resistance between Mo and CIG. More preferably, the present application selects double-layer Mo as the material of the back electrode layer, which has good adhesion to the substrate and higher conductivity.

[0104] The inventors found in their research that the buffer layer material selected in this application can better reduce the band gap step and lattice mismatch rate between the CIGS absorption layer and the high resistance layer, and at the same time protect the CIGS absorption layer. The high resistance layer material selected in this application has high transmittance and resistivity, can pass through most of the solar spectrum, and can achieve lattice matching between the high resistance layer and the buffer layer; when used with the material of the transparent conductive layer of this application, it can also ensure that most of the solar spectrum is passed through, and can better collect current, reduce resistance, and improve the photoelectric conversion efficiency of CIGS power generation glass.

[0105] Preferably, the buffer layer 124 is indium sulfide or cadmium sulfide doped with a small amount of sodium chloride (sodium sulfide), wherein the atomic fraction ratio of S:Na:In(Cd):Cl is 40-50:10-15:30-40:10-15.

[0106] Preferably, the light transmittance of the high resistance layer 125 is between 70% and 90%.

[0107] Preferably, the light transmittance of the transparent conductive layer 126 is between 70% and 90%, and the square resistance is less than 15Ω.

[0108] Preferably, the thickness of the substrate 121 is 2 to 4 mm; the thickness of the back electrode layer 122 is 0.2 to 1 μm; the thickness of the absorption layer 123 is 1.5 to 2.0 μm; the thickness of the buffer layer 124 is 0.05 to 0.1 μm; the thickness of the high resistance layer 125 is 0.05 to 0.1 μm; and the thickness of the transparent conductive layer 126 is 0.5 to 1.5 μm.

[0109] Preferably, the back electrode layer 122 is composed of a double layer of Mo, the thickness of the first layer of Mo is 150-250 nm, and the thickness of the second layer of Mo is 40-100 nm.

[0110] The inventors found in their research that the thicknesses of the substrate 121 , the back electrode layer 122 , the absorption layer 123 , the buffer layer 124 , the high resistance layer 125 and the transparent conductive layer 126 are within the scope of the present application, which improves the photoelectric conversion efficiency of the CIGS power generation glass.

[0111] In the present application, in order to ensure the quality of Mo thin film deposition, the step of pre-treating the substrate 121 may also be included, including: washing with deionized water, and then drying the surface moisture with N2 or purified dry air (CDA).

[0112] Preferably, the substrate 121 is prepared by a float process, a calendaring process or an overflow down-draw process;

[0113] The back electrode layer 122 is prepared by magnetron sputtering, chemical vapor deposition or electroplating;

[0114] The CIGS absorption layer 1231 is prepared by a sputtering and then selenization method or a co-evaporation method;

[0115] The buffer layer 124 is prepared by evaporation or chemical bath deposition;

[0116] The high resistance layer 125 is prepared by radio frequency magnetron sputtering or pulsed DC sputtering;

[0117] The transparent conductive layer 126 is prepared by direct current magnetron sputtering, pulsed direct current sputtering or radio frequency magnetron sputtering.

[0118] In the present application, there is no particular limitation on the specific method of preparing the substrate 121 by float process, calendering process or overflow down-draw process, as long as the purpose of the present application can be achieved. Preferably, soda-lime glass can be prepared by adopting float process, and the specific steps can be: pouring molten glass on a narrow tin bath, the surface tension of the glass makes it float on the tin and stretch flatly and evenly, and naturally set in reducing air, this process can ensure that the glass sheet forms an extremely parallel and flat surface.

[0119] The inventors found in their research that the back electrode layer 122 is prepared by magnetron sputtering, chemical vapor deposition or electroplating, which can achieve higher film uniformity, improve the coverage ability of the film, and have higher purity, density and adhesion. In the present application, there is no special restriction on the type of magnetron sputtering, and different sputtering methods can be selected according to the type of target material. For example, when sputtering a metal target, DC magnetron sputtering is usually selected. When the sputtering target is a semiconductor or an insulator, RF magnetron sputtering is usually selected. In the present application, there is no special restriction on the specific method of magnetron sputtering, as long as the purpose of this application can be achieved. For example, the basic process parameters for preparing Mo film by magnetron sputtering can be: the limit vacuum degree is 5×10 -5 mbar, working pressure is 5×10 -3 mbar, the target-substrate distance is 50-100mm, and the deposition temperature is 30-70°C. In the present application, there is no particular restriction on the specific method of preparing the back electrode layer 122 by chemical vapor deposition or electroplating, as long as the purpose of the present application can be achieved. For example, the Mo back electrode can be prepared using the patented technology of ZL201721026913.6. The Mo back electrode is sequentially provided with a metal conductive layer, a barrier layer, a Na alloy layer and an outer protective conductive layer from bottom to top; the barrier layer is a transition metal nitride or a nitrogen oxide; and the outer protective conductive layer is Mo. The barrier layer can prevent Na from diffusing toward the substrate, and also prevent impurities in the substrate from diffusing toward the copper indium gallium selenide light absorption layer, thereby achieving precise control of Na. In addition, the barrier layer also prevents the diffusion of selenium elements into the metal conductive layer during the deposition process, thereby avoiding the reaction between selenium and the metal conductive layer, and ensuring the stability of the metal conductive layer during the generation of the copper indium gallium selenide light absorption layer. More preferably, according to the preparation process provided by patent ZL201610897536.7, a layer of niobium (Nb) metal film is prepared on the double-layer Mo electrode by sputtering or evaporation, which can effectively improve the adhesion between the back electrode and the absorption layer.

[0120] In the present application, there is no particular limitation on the specific method of preparing the CIGS absorption layer 1231 by the sputtering and then selenization method or the co-evaporation method, as long as the purpose of the present application can be achieved.

[0121] Preferably, the steps of preparing the CIGS absorption layer 1231 by the sputtering and then selenization method include:

[0122] Sputtering copper, indium, gallium and sodium onto the upper surface of the back electrode layer 122 by a DC magnetron sputtering method at an atomic fraction ratio of 50-55:30-35:10-15:0.1-0.5;

[0123] By evaporation, selenium particles are evaporated into selenium vapor, and then evaporated onto the surface of the back electrode layer on which copper, indium, gallium and sodium are sputtered, so as to obtain a CIGS prefabricated layer; in the CIGS prefabricated layer, the atomic fraction ratio of the five elements of copper, indium, gallium, selenium and sodium is 25-30:15-25:5-10:34-53:1-2;

[0124] The CIGS prefabricated layer is heated to 500-600° C. by infrared heating to obtain the CIGS absorption layer 1231 .

[0125] In the present application, there is no particular limitation on the specific method of DC magnetron sputtering, as long as the purpose of the invention can be achieved. For example, the basic process parameters for preparing the CIGS absorption layer by magnetron sputtering can be: the ultimate vacuum degree is 2×10 -6 mbar, working pressure is 5×10 -3 mbar, the target-substrate distance is 50-100 mm, and the deposition temperature is 30-70 °C.

[0126] In the present application, there is no particular limitation on the specific method of the evaporation method, as long as the purpose of the invention can be achieved. For example, the evaporation rate of selenium is 10-100 nm / s.

[0127] In the present application, there is no particular limitation on the specific method of infrared heating, as long as the purpose of the invention can be achieved. For example, a quartz lamp tube with a tungsten filament jacket is used as a light source started by a high-power power supply, 20 to 30 quartz lamp tubes are placed above and below the CIGS prefabricated layer, each lamp tube has a power output of 3000 to 14000 W, and the total power output of the upper and lower power supplies is within the range of 60000-90000 W, with a wavelength of 0.76 to 5 μm.

[0128] The inventors discovered in their research that the CIGS absorption layer 1231 is prepared by a sputtering-post-selenization method. During the sputtering process, it is relatively easy to control the stoichiometric ratio of each element in the film. Not only is the film uniformly distributed in composition, but the thickness is also relatively uniform, and each element can be adjusted and improved at different positions. Moreover, the CIGS absorption layer prepared by the sputtering-post-selenization method contains the sodium element. The introduction of an appropriate amount of alkaline metals can increase the carrier concentration and increase the power of the CIGS power generation glass.

[0129] Preferably, the steps of preparing the CIGS absorption layer 1231 by the co-evaporation method include:

[0130] In a selenium atmosphere, when the temperature of the substrate 121 is 300-400° C., indium / gallium is co-evaporated and deposited at a deposition rate of 30-50 nm / min for 20-30 min; the atomic fraction ratio of indium:gallium:selenium is 10-20:5-10:70-85;

[0131] The temperature of the substrate 121 is raised to 500-600° C., and copper is evaporated and deposited at a deposition rate of 50-70 nm / min. When the substrate has a cooling point, the deposition is terminated for 15-25 min. The atomic fraction ratio of copper: indium: gallium: selenium is 28-35:8-15:4-7:40-58.

[0132] The temperature of the substrate 121 is maintained at 500-600° C., and indium / gallium is deposited by co-evaporation compensation at a deposition rate of 30-50 nm / min for 2-5 min to obtain the CIGS absorption layer 1231 .

[0133] It should be noted that the cooling point of the substrate refers to the inflection point where the substrate temperature suddenly drops, which can be determined by the temperature drop rate. In the present application, a cooling point occurs when the substrate temperature drops by more than 5°C / min.

[0134] The inventors discovered in their research that the three-step co-evaporation method of the present application can form a V-type Ga concentration gradient by preparing the CIGS absorption layer 1231, which not only absorbs long-wave light more fully, but also forms a back electric field that promotes the separation of photogenerated carriers, thereby improving the photoelectric conversion efficiency of the CIGS power generation glass.

[0135] In the present application, there is no particular limitation on the specific method of preparing the buffer layer 124 by evaporation or chemical water bath deposition, as long as the purpose of the present application can be achieved. Optionally, the chalcogenide semiconductor buffer layer 124 is prepared by using the patented technologies of ZL201480047433.0 and ZL201380032809.6, and the buffer layer 124 is prepared by evaporation at an evaporation rate of 10 to 30 nm / s, and the obtained buffer layer 124 is indium sulfide or cadmium sulfide doped with a small amount of sodium chloride (sodium sulfide), wherein the atomic fraction ratio of S:Na:In(Cd):Cl is 40 to 50:10 to 15:30 to 40:10 to 15.

[0136] In the present application, there is no particular limitation on the specific method of preparing the high resistance layer 125 by the radio frequency magnetron sputtering method or the pulsed DC sputtering method, as long as the purpose of the present application can be achieved; preferably, the high resistance layer 125 is prepared by the radio frequency magnetron sputtering method, and its basic process parameters can be: the background vacuum degree is 2×10 -6 mbar, working pressure is 5×10 -3mbar, the target-substrate distance is 50-100 mm, and the deposition temperature is 70-120° C. The prepared high resistance layer 125 is intrinsic zinc oxide or magnesium-doped zinc oxide or aluminum-doped zinc oxide with a thickness of 0.05-0.1 μm, and its light transmittance is between 70% and 90%.

[0137] There is no particular limitation on the specific method of preparing the transparent conductive layer 126 by DC magnetron sputtering, pulsed DC sputtering or radio frequency magnetron sputtering, as long as the purpose of the present application can be achieved. For example, the transparent conductive layer 126 is prepared by DC magnetron sputtering, and its basic process parameters can be: the background vacuum degree is 2×10 -6 mbar, working pressure is 5×10 - 3 mbar, the target-substrate distance is 50-100mm, and the deposition temperature is 170-230°C. The prepared transparent conductive layer 126 is aluminum-doped zinc oxide, boron-doped zinc oxide or indium tin oxide with a thickness of 0.5-1.5μm, so that its light transmittance is between 70% and 90%, and the square resistance is less than 15Ω. The transparent conductive layer 126 can be prepared using the patented technology of CN201711486714.8, including two film layers, from bottom to top, 5-25nm aluminum-based film layer and 5-10nm molybdenum-based film layer, with low square resistance, high visible light transmittance, and thin film thickness.

[0138] Preferably, the preparation method of the CIGS power generation glass may further include preparing a marble or wood pattern component on the transparent conductive layer 126. Using the patent technology of ZL202280001100.9, a stone or wood pattern is obtained by scanning the surface of the stone or wood by digital image, and the background area in the stone or wood pattern is removed to obtain a stone or wood texture pattern; the stone or wood texture pattern is passed onto the surface of the glass cover facing the lamination layer or the surface of the glass cover facing the outside to obtain an imitation stone or wood pattern; the imitation stone or wood pattern is cured; and the glass cover with the imitation stone or wood pattern is laminated onto the photovoltaic stack.

[0139] Preferably, the preparation method of the CIGS power generation glass may also include laser scribing. Laser scribing is performed using the patent technology of ZL201610897538.6. The first laser scribing system and the second laser scribing system are respectively arranged in the scribing direction to form a double laser scribing system in parallel; the first laser scribing system is started to scribble the first scribing line to scribble the back electrode layer 122 and separate the back electrode layer 122; the absorption layer 123 is grown on the back electrode layer 122; the double laser scribing system is started to scribble the second scribing line to scribble the absorption layer 123 to provide a channel connecting the front and rear electrodes; the first laser scribing system and the second laser scribing system are scribed simultaneously and synchronously, and the repetition frequency of the first laser scribing system is lower than the repetition frequency of the second laser scribing system; the buffer layer 124 and the high resistance layer 125, and the transparent conductive layer 126 are sputtered on the absorption layer 123; the double laser scribing system is started to scribble the third scribing line to scribble the transparent conductive layer 126 from the absorption layer 123 to form an internal series structure.

[0140] Preferably, the preparation method of the CIGS power generation glass further includes: installing the busbar. The busbar is welded using the patented technology and device of ZL202011479832.8. The traction assembly pulls the busbar to the end of the bottom plate, and the end block presses the end of the busbar; the welding block presses the busbar, and the welding assembly welds the busbar and the back electrode layer 122 to form a weld; the frame moves right to feed the material, and the traction block presses the busbar at the same time. After one welding is completed, the welding block and the welding assembly move right together with the random frame. Repeat the above actions until the welding is completed, and cut the busbar.

[0141] Preferably, the preparation method of the CIGS power generation glass further comprises: sealing. The present application has no particular limitation on the specific method of sealing, as long as the purpose of the present application can be achieved. For example, ethylene-vinyl acetate copolymer (EVA) or polyethylene octene copolymer (POE) is used for sealing.

[0142] Preferably, the preparation method of the CIGS power generation glass also includes: lamination. The present application has no particular restrictions on the specific method of lamination, as long as the purpose of the present application can be achieved. For example, tempered glass is used for laminated glass, hollow glass, three-glass two-chamber glass, etc. to laminate and laminate to obtain a component. Optionally, the patented technology ZL201610897537.1 applied by the inventor can be used to prepare super-hydrophobic solar cell cover glass. First, the solidified polydimethylsiloxane and cover glass are placed in an evaporation chamber for co-evaporation coating. The temperature is 200-300°C, and the co-evaporation time is 2-8 hours. The mass of the polydimethylsiloxane material is 5-10g. After slowly cooling, the cover glass is taken out to obtain a super-hydrophobic solar cell cover glass.

[0143] Preferably, the percentage of the number of S element atoms on the surface of the absorption layer 123 after vulcanization to the total number of atoms of the surface elements of the absorption layer 123 after vulcanization is 6-10%, preferably 6-8%, and more preferably 6-7%; the percentage of the mass of S element at the bottom of the absorption layer 123 after vulcanization to the total mass of the bottom of the absorption layer 123 after vulcanization is ≤0.03%.

[0144] In the present application, the surface of the absorption layer 123 is the upper surface of the absorption layer; the bottom of the absorption layer 123 is the upper surface after the absorption layer 123 is immersed in a 5-20wt% aminosulfonic acid aqueous solution for 2-3 minutes to corrode the metal layer on the surface of the absorption layer.

[0145] The fourth aspect of the present application provides a device for preparing CIGS power generation glass, which includes the sulfurization device described in the second aspect of the present application.

[0146] The fifth aspect of the present application provides CIGS power generation glass prepared by the preparation method described in the third aspect of the present application or the preparation device described in the fourth aspect of the present application.

[0147] The method and device for sulfurizing the surface of the CIGS absorption layer provided in the present application can limit the reaction depth of the S element replacing the Se element by sulfurizing the surface of the CIGS absorption layer by using a laser heating method, so that sulfurization occurs on the surface of the CIGS absorption layer, avoiding excessive S content inside and at the bottom of the CIGS absorption layer, and avoiding excessive MoS2 with poorer conductivity at the bottom of the CIGS absorption layer, so that the Ga at the bottom of the CIGS absorption layer and the S at the top of the CIGS absorption layer form a "V"-shaped gradient band gap, which enhances electron transmission, increases the open circuit voltage and fill factor, and thus improves the photoelectric conversion efficiency of the CIGS power generation glass. The present application further provides a method for preparing CIGS power generation glass, a preparation device, and CIGS power generation glass, and the cell has a high conversion efficiency.

[0148] Example

[0149] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0150] Test method:

[0151] Electrical performance test method:

[0152] Test methods for maximum power (Pmpp), open circuit voltage (Voc), short circuit current (Isc), parallel resistance (Rsh), series resistance (Rs), fill factor (FF), and photoelectric conversion efficiency (Eta):

[0153] Preparation before the test: Make sure that the test machine environment and conditions meet the test requirements. This test uses the AM1.5G standard conditions. The test machine is produced by the German HALM company and its model is: A-172469 test machine;

[0154] Test process: Place the finished components into the test machine, connect the test circuit, measure the current and power output of the CIGS photovoltaic component at different voltages of 0 to 90V through the test equipment, and record the corresponding current (I) and voltage (V) values.

[0155] Data analysis: Based on these data, draw an IV curve. According to the IV curve, get Pm pp , Rsh, Rs, Voc and Isc, and then through the formula FF = Pm PP / (Voc×Isc), Eta=(FF×Voc×Isc) / (Pin×S) to calculate FF and Eta. Pin is the incident light energy density, which is 1000±50W / m 2 ; S is the battery area, 1.05±0.01mm 2 .

[0156] Element analysis of the absorption layer membrane surface:

[0157] The absorption layer elements of CIGS power generation glass are analyzed by wavelength dispersive fluorescence spectrometer (WDX). When the primary X-rays irradiate the sample, the inner electrons of the excited atoms produce energy level transitions and emit characteristic secondary X-rays. The energy and intensity of the secondary X-rays can be detected and are related to the content of the element to be measured in the sample, so the element can be qualitatively and quantitatively analyzed.

[0158] Analysis of element concentration at the bottom of the absorption layer:

[0159] Take a substrate including an absorption layer with sulfurized surface, soak it in a 10 wt % aminosulfonic acid aqueous solution for 2-3 minutes to corrode the metal layer on the surface of the absorption layer, and then analyze the elements at the bottom of the absorption layer by WDX.

[0160] Example 1

[0161] like Figure 1As shown, the vulcanization device for the surface of the CIGS absorption layer includes: a transmission cavity 1, the transmission cavity 1 is connected to an exhaust system 5, an inert gas intake system 3 and a sulfur-containing gas intake system 4, the transmission cavity 1 is provided with a laser emitter 6 with a Dammann grating 7 and a transmission device 9, the transmission device 9 transmits the substrate 10 including the CIGS absorption layer to the transmission cavity 1, and the target laser emitted by the laser emitter 6 is irradiated to the surface of the copper indium gallium selenide absorption layer through the Dammann grating 7; the first cavity flap valve 2 and the second cavity flap valve 8 are respectively provided on both sides of the transmission cavity 1. The preparation process flow chart of CIGS power generation glass is shown in FIG. Figure 3 shown.

[0162] (1) Soda-lime glass with a size of 1583 mm×660 mm (thickness of 3 mm) was selected as a substrate, which was first rinsed repeatedly with deionized water and then dried with an air knife; two Mo layers were then plated on the substrate in sequence by magnetron sputtering, the thickness of the first Mo film was 160 nm; the thickness of the second Mo film was 45 nm to form a Mo back electrode layer; the Mo back electrode layer 122 was etched through by laser to form 137 sub-battery units, and the size of the sub-battery was 1580×5.6 mm;

[0163] (2) DC magnetron sputtering was used to deposit 5×10 -3 In an Ar atmosphere of mbar, copper, indium, gallium and sodium are sputtered onto the upper surface of the back electrode layer at an atomic fraction ratio of 52:32:12:0.2, with a thickness of 0.8 nm; the sputtering power of copper is 12 kwh; the sputtering power of indium is 10 kwh; the sputtering power density of gallium is 12 kwh; and the sputtering power density of sodium is 5 kwh;

[0164] By evaporation, the selenium particles are evaporated into selenium vapor according to the atomic fraction ratio of copper, indium, gallium, selenium and sodium of 27:20:7:45:1, and then evaporated at a rate of 20nm / s onto the surface of the back electrode layer on which copper, indium, gallium and sodium have been sputtered, to obtain a CIGS prefabricated layer with a thickness of 1500nm; by infrared heating, the CIGS prefabricated layer is heated to 550-600℃ to obtain the CIGS absorption layer (CuIn 1-x Ga x Se2 absorption layer, because Ga is substituted for In, so x is the amount of substitution);

[0165] (3) Using the above-mentioned vulcanization device, the transfer chamber 1 is placed in a slightly negative pressure state through the exhaust system 5; N2 is introduced through the inert gas intake system 3 to adjust the pressure of the transfer chamber 1 to 500 mbar; the exhaust system 5 is then used to adjust the pressure of the transfer chamber 1 to 5 mbar, and the above steps are repeated three times. Finally, the exhaust system 5 is used to adjust the pressure of the transfer chamber 1 to 0.1 mbar; the first flap valve 2 is opened, and the transfer device 9 transfers the substrate 10 including the CIGS absorption layer to the transfer chamber 1;

[0166] The inert gas inlet system 3 and the sulfur-containing gas inlet system 4 are turned on, and N2 and H2S are input into the transfer chamber 1. In the atmosphere of N2 and H2S, the target laser emitted by the laser emitter 6 is irradiated to the surface of the CIGS absorption layer in a dot matrix through the Dammann grating 7, so that the temperature of the surface of the CIGS absorption layer rises to 550-600°C at a rate of 40-50°C / s for heating;

[0167] N2 is introduced through the inert gas inlet system 3 to adjust the pressure of the transfer chamber 1 to 500 mbar; the pressure of the transfer chamber 1 is adjusted to 5 mbar through the exhaust system 5, and the above steps are repeated three times, and finally the pressure of the transfer chamber 1 is adjusted to 0.1 mbar through the exhaust system 5;

[0168] The laser emitter 6 is turned off, and the air is circulated through the air extraction system 5 to evacuate and release air, and then the surface temperature is reduced to 20-100° C. to obtain a vulcanized layer; the second flap valve 8 is opened, and the conveying device 9 conveys the substrate 10 including the CIGS absorption layer to the outside of the conveying chamber 1 to complete the vulcanization;

[0169] The volume ratio of H2S and N2 is 1:2; the wavelength of the dot laser is 10.6μm, the scanning speed is 25mm / s, and the output power is 80W;

[0170] (4) cleaning the substrate including the surface-sulfurized absorption layer, and evaporating an indium sulfide buffer layer (In2S3 buffer layer) doped with a small amount of sodium chloride on the surface-sulfurized absorption layer at an evaporation rate of 20 nm / s, wherein the atomic fraction ratio of S:Na:In:Cl is 45:10:35:10; the thickness of the indium sulfide buffer layer is 80 nm;

[0171] (5) depositing an intrinsic zinc oxide high resistance layer (i-ZnO layer) with a thickness of 80 nm on the indium sulfide buffer layer by radio frequency magnetron sputtering;

[0172] (6) Using a picosecond laser with a power of 1.5 W and a frequency of 1000 kHz, the CIGS absorption layer, In2S3 buffer layer and i-ZnO layer are scribed without damaging the Mo back electrode layer, providing a current transmission channel to form 137 sub-battery units. The entire chip is 1580×660 mm, of which each sub-battery has a size of 1564×4.5 mm. The excess part is the edge cleaning distance to provide a subsequent front electrode aluminum-doped zinc oxide (AZO) and Mo electrode interconnection channel;

[0173] (7) depositing an aluminum-doped zinc oxide (AZO) transparent conductive layer (front electrode) with a thickness of 1 μm on the i-ZnO high resistance layer by magnetron sputtering;

[0174] (8) Use a sharp needle to mechanically scratch the deposited AZO film into small pieces of specified size as needed. The small pieces serve as the window layer and front electrode of the CIGS battery. Then, by installing bus bars on both sides of the substrate to draw out the current, CIGS power generation glass can be obtained.

[0175] Example 2

[0176] In addition to replacing step (2) with “In a selenium atmosphere, at a substrate temperature of 350° C., co-evaporation deposits indium / gallium at a deposition rate of 40 nm / min for 25 min; wherein the atomic fraction ratio of indium:gallium:selenium is 15:5:80;

[0177] The substrate temperature was raised to 550°C, and copper was evaporated and deposited at a deposition rate of 60nm / min. The deposition was terminated when the substrate showed a cooling point, and the duration was 20min. The atomic fraction ratio of copper: indium: gallium: selenium was 34:13:6:47.

[0178] The substrate temperature was maintained at 550° C., and indium / gallium was deposited by co-evaporation compensation at a deposition rate of 40 nm / min for 5 min to obtain the CIGS absorption layer. The rest was the same as in Example 1.

[0179] Example 3

[0180] Except that H2S in step (3) is replaced by sulfur vapor, the rest is the same as Example 1.

[0181] Example 4

[0182] Except that N2 in step (3) is replaced by helium, the rest is the same as Example 1.

[0183] Example 5

[0184] Except that in step (3), "the volume ratio of H2S and N2 is 1:2" is replaced by "the volume ratio of H2S and N2 is 1:5", the rest is the same as Example 1.

[0185] Example 6

[0186] Except for replacing "the wavelength of the dot matrix laser is 10.6 μm, the scanning speed is 25 mm / s, and the output power is 80 W" in step (3) with "the wavelength of the dot matrix laser is 5 μm, the scanning speed is 15 mm / s, and the output power is 50 W", the rest is the same as Example 1.

[0187] Example 7

[0188] The same procedures as in Example 1 are as follows except that in step (3), "the temperature of the surface of the CIGS absorption layer is raised to 550-600°C at a rate of 40-50°C / s and heated" is replaced by "the temperature of the surface of the CIGS absorption layer is raised to 550-600°C at a rate of 20-30°C / s and heated".

[0189] Example 8

[0190] The same procedures as in Example 1 are as follows except that in step (3), "the temperature of the surface of the CIGS absorption layer is raised to 550-600°C at a rate of 40-50°C / s and heated" is replaced by "the temperature of the surface of the CIGS absorption layer is raised to 550-600°C at a rate of 60-70°C / s and heated".

[0191] Comparative Example 1

[0192] In addition to replacing the dot matrix laser heating in step (3) with infrared heating, tungsten filament sheathed quartz lamps are used as the light source for starting a high-power power supply. There are 20 to 30 quartz lamps on the upper and lower sides of the substrate including the CIGS absorption layer. The output power of each lamp is 3000 to 14000 W. The total output power of the upper and lower power supplies is in the range of 60000-90000 W. The wavelength range is between 0.76-5 um. The rest is the same as in Example 1.

[0193] Comparative Example 2

[0194] In addition to replacing the dot matrix laser heating in step (3) with infrared heating, tungsten filament sheathed quartz lamps are used as light sources for starting a high-power power supply. There are 20 to 30 quartz lamps on the upper and lower sides of the substrate including the CIGS absorption layer. The output power of each lamp is 3000 to 14000 W. The total output power of the upper and lower power supplies is in the range of 60000-90000 W. The wavelength range is between 0.76-5 um. The rest is the same as in Example 2.

[0195] The electrical performance test results of the CIGS power generation glass of Examples 1-8, Comparative Example 1 and Comparative Example 2 are shown in Table 1.

[0196] Table 1 Electrical performance parameters

[0197]

[0198]

[0199] As can be seen from Table 1, the performance of CIGS power generation glass prepared by the method of the present application is significantly improved. The fill factor FF of the open circuit voltage Voc is a measure of the comparison between the maximum power area contained in the IV characteristic curve of the solar cell and the rectangular area (ideal shape) corresponding to the open circuit and short circuit. Obviously, FF should be as close to 1 (i.e. 100%) as possible, but the pn junction characteristics of the exponential function prevent it from reaching 1. The larger the FF, the higher the quality of the solar cell. When the series resistance increases, the short-circuit current of the solar cell will decrease, because a voltage drop will be generated when the current passes through the resistor, resulting in a decrease in the effective voltage of the battery, thereby reducing the photoelectric conversion efficiency of the solar cell. At the same time, an increase in series resistance will also reduce the fill factor of the solar cell, because the fill factor is the ratio of the maximum output power of the solar cell to the ideal output power, and the ideal output power is the output power when the battery is assumed to have no internal resistance. Therefore, the larger the series resistance, the greater the gap between the ideal output power and the maximum output power, and the smaller the fill factor. The fill factor is an important parameter for evaluating the output characteristics of solar cells, and it directly determines the output power of solar cells. Therefore, the smaller the series resistance, the larger the fill factor, and the higher the output power. The parallel resistance is mainly due to the imperfect pn junction or impurities near the junction, which can cause the junction to short-circuit, especially at the edge of the battery. The parallel resistance reflects the leakage level of the battery. The smaller the parallel resistance, the greater the output current of the solar cell and the higher the output power. The FF in Examples 1-8 is higher than that in Comparative Examples 1 and 2, which reduces the carrier recombination at the interface of the space charge region, and the corresponding photoelectric conversion efficiency is also higher than that in Comparative Examples 1 and 2. It is explained that by using a dot matrix laser to perform sulfurization treatment on the surface of the absorption layer, electron transmission is enhanced, the open circuit voltage and fill factor are increased, and the photoelectric conversion efficiency of CIGS power generation glass is improved.

[0200] The surface element analysis results of the CIGS absorption layer of Examples 1-8, Comparative Example 1 and Comparative Example 2 are shown in Table 2.

[0201] Table 2 Distribution of atomic ratios of elements on the surface of the absorption layer

[0202]

[0203]

[0204] Note: In Table 2, “at%” means atomic percentage.

[0205] The analysis results of the elements at the bottom of the CIGS absorption layer of Examples 1-8, Comparative Example 1 and Comparative Example 2 are shown in Table 3.

[0206] Table 3 Atomic percentage of elements at the bottom of the absorption layer

[0207]

[0208] It can be seen from Tables 2 to 3 that the percentage of the number of S element atoms on the surface of the absorption layer of the CIGS power generation glass prepared in Examples 1-8 after sulfurization accounts for more than 6% of the total number of atoms of the absorption layer surface after sulfurization, which is much higher than that of Comparative Examples 1 and 2; and the percentage of the mass of S element at the bottom of the absorption layer after sulfurization in Examples 1-8 accounts for the total mass of the elements at the bottom of the absorption layer after sulfurization is ≤0.04%, which shows that by using laser sulfurization treatment on the surface of the absorption layer, the reaction depth of S element replacing Se element can be limited, and sulfurization can be allowed to occur on the surface of the CIGS absorption layer, making the sulfurization more complete, avoiding excessive S content inside and at the bottom of the CIGS absorption layer, and avoiding the generation of too much MoS2 with poorer conductivity at the bottom of the CIGS absorption layer, so that the Ga at the bottom of the absorption layer and the S at the top of the absorption layer form a "V"-shaped gradient band gap, thereby improving the photoelectric conversion efficiency of the CIGS power generation glass.

[0209] In summary, the sulfurization method and device for the surface of the CIGS absorption layer provided in the present application, by using laser to perform sulfurization treatment on the surface of the absorption layer, can limit the reaction depth of the S element replacing the Se element, allow sulfurization to occur on the surface of the CIGS absorption layer, avoid excessive S content inside and at the bottom of the CIGS absorption layer, and avoid excessive MoS2 with poorer conductivity at the bottom of the CIGS absorption layer, so that the Ga at the bottom of the absorption layer and the S at the top of the absorption layer form a "V"-shaped gradient band gap, enhance electron transmission, increase the open circuit voltage and fill factor, and thus improve the photoelectric conversion efficiency of the CIGS power generation glass.

[0210] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A method for sulfurizing the surface of a copper indium gallium selenide absorber layer, comprising: The substrate including the copper indium gallium selenide absorption layer is cooled to 20-100°C; in an atmosphere of sulfur-containing gas and inert gas, the temperature of the surface of the copper indium gallium selenide absorption layer is raised to 550-600°C by laser heating, and then cooled to 20-100°C to obtain a sulfide layer.

2. The vulcanization method according to claim 1, wherein The laser heating method adopts dot matrix laser heating.

3. The vulcanization method according to claim 1, wherein The volume ratio of the sulfur-containing gas to the inert gas is 1:2 to 1:

3.

4. The vulcanization method according to claim 1, wherein The laser heating method has a laser wavelength of 8 to 12 μm, a scanning speed of 20 to 30 mm / s, and an output power of 60 to 100 W.

5. The vulcanization method according to claim 1, wherein The laser irradiation depth of the laser heating method is 1.0 to 2.0 μm.

6. The vulcanization method according to claim 1, wherein The sulfur-containing gas is selected from at least one of H2S and sulfur vapor; and the inert gas is selected from at least one of nitrogen, argon and helium.

7. The vulcanization method according to claim 1, wherein The heating rate of the laser heating method is 40-50°C / s.

8. The vulcanization method according to claim 1, wherein The percentage of the number of S element atoms on the surface of the sulfurized absorption layer accounts for 6-10% of the total number of atoms of the surface elements of the sulfurized absorption layer; the percentage of the mass of S element at the bottom of the sulfurized absorption layer accounts for ≤0.03% of the total mass of the bottom of the sulfurized absorption layer.

9. A device for sulfurizing the surface of a copper indium gallium selenide absorption layer, comprising: A transmission cavity is provided, wherein an exhaust system, an inert gas intake system and a sulfur-containing gas intake system are connected to the outside of the transmission cavity. A laser emitter, a Dammann grating and a transmission device are provided in the transmission cavity. The transmission device transmits a substrate including a copper indium gallium selenide absorption layer into the transmission cavity. The target laser emitted by the laser emitter is irradiated onto the surface of the copper indium gallium selenide absorption layer through the Dammann grating.

10. The vulcanizing device according to claim 9, wherein: A first cavity flap valve and a second cavity flap valve are respectively provided on both sides of the transfer cavity.

11. The vulcanizing device according to claim 9, wherein: The sulfur-containing gas intake system is selected from at least one of an H2S intake system and a sulfur vapor intake system; the inert gas intake system is selected from at least one of a nitrogen intake system, an argon intake system and a helium intake system.

12. The vulcanizing device according to claim 9, wherein: The Dammann grating is rotatable so that the included angle α between the target laser and the Dammann grating satisfies 0°<α≤90°.

13. A method for preparing copper indium gallium selenide power generation glass, comprising: preparing a substrate, and preparing a back electrode layer on the upper surface of the substrate; preparing a copper indium gallium selenide absorption layer on the upper surface of the back electrode layer; Sulfurizing the surface of the copper indium gallium selenide absorber layer, comprising: sulfurizing the surface of the copper indium gallium selenide absorber layer using the sulfurization method according to any one of claims 1 to 8 or the sulfurization device according to any one of claims 9 to 12 to obtain the sulfurized layer; preparing a buffer layer on the upper surface of the vulcanized layer; preparing a high resistance layer on the upper surface of the buffer layer; preparing a transparent conductive layer on the upper surface of the high resistance layer; The copper indium gallium selenide power generation glass is obtained by installing bus bars on both sides of the substrate to draw out current.

14. The preparation method according to claim 13, wherein The material of the substrate is selected from soda-lime glass, flexible metal foil or polyimide; the material of the back electrode layer is selected from molybdenum, copper zinc or nickel; the material of the buffer layer is selected from indium sulfide or cadmium sulfide; the material of the high resistance layer is selected from intrinsic zinc oxide or magnesium-doped zinc oxide; the material of the transparent conductive layer is selected from aluminum-doped zinc oxide, boron-doped zinc oxide or indium tin oxide.

15. The preparation method according to claim 13, wherein The thickness of the substrate is 2 to 4 mm; the thickness of the back electrode layer is 0.2 to 1 μm; the thickness of the absorption layer is 1.5 to 2.0 μm; the thickness of the buffer layer is 0.05 to 0.1 μm; the thickness of the high-resistance layer is 0.05 to 0.1 μm; and the thickness of the transparent conductive layer is 0.5 to 1.5 μm.

16. The preparation method according to claim 13, wherein The substrate is prepared by a float method, a calendaring method or an overflow down-draw method; The back electrode layer is prepared by magnetron sputtering, chemical vapor deposition or electroplating; The copper indium gallium selenide absorption layer is prepared by a sputtering and then selenization method or a co-evaporation method; The buffer layer is prepared by evaporation or chemical water bath deposition; The high resistance layer is prepared by radio frequency magnetron sputtering or pulsed DC sputtering; The transparent conductive layer is prepared by a DC magnetron sputtering method, a pulsed DC sputtering method or a radio frequency magnetron sputtering method.

17. A device for preparing copper indium gallium selenide power generation glass, comprising the sulfurization device according to any one of claims 9 to 12.

18. Copper indium gallium selenide power generation glass prepared by the preparation method according to any one of claims 13 to 16 or the preparation device according to claim 17.

Citation Information

Patent Citations

  • Preparation method of light absorption layer of film solar cell

    CN110571155A

  • Copper-indium-gallium-selenium thin-film solar cell absorption layer surface treatment device

    CN111029423A

  • Low cost solar cells formed using a chalcogenization rate modifier

    US20110294254A1

  • Laser annealing for thin film solar cells

    US20130065355A1